Requests, Issuing, and Hospital Admissions Regarding Mental Health Warrants Before and During the COVID-19 Pandemic in a Region in Portugal - Ricoca Peixoto, Vasco (2023)
Introduction: Mental health warrants exist in most countries and are issued when patients have severe mental illness, refuse treatment, and present a serious risk to themselves or others. We describe the epidemiology of mental health warrant requests received, and warrants issued by a Public Health Unit in a Portuguese region, as well as subsequent hospital admissions before and during the COVID-19 pandemic.Methods: We used routine administrative data of mental health warrant request entries from a Public Health Unit serving a population of 219 739 individuals and compared the average of monthly requests, issued warrants, and hospital admissions during two separate periods (January 2013 to January 2021 and February 2021 to October 2022) as well as the proportion of warrants issued, hospital admissions among requests, and other patient characteristics. We identified factors associated with hospital admissions among the requests using logistic regression.Results: Monthly average warrant requests, issued warrants and hospital admissions increased after February 2021 (x̄ 2.87 vs 7.09 p < 0.001; x̄ 2.67 vs 6.42 p < 0.001; x̄ 1.55 vs 3.58 p < 0.001). We found no differences by period in the proportion of requests with issued warrants (92.8% vs 90.6% p = 0.42) nor the proportion of requests with subsequent hospital admissions (54.0% vs 49.0% p = 0.33). In the second period, there were differences in the proportion of patients with a previously diagnosed mental health disorder (95.3% vs 90.4% p = 0.049). There were significant differences in the distribution of the origin of requests. Being unemployed (OR:2.5 CI:1.2 - 5.2), not having completed high school (OR:2.01 CI:1.12 - 3.77) and having university education (OR:3.67 CI:1.27 - 10.57) degree were associated with hospital admission.Conclusion: Severe mental illness with criteria for mental health warrants may require more resources and different approaches due to a possible increase during and after the COVID-19 pandemic. Community based mental healthcare, incentivized follow-up by primary care and ambulatory treatment may be considered. Further research should evaluate both the national and international trends and associated factors.